Characterization of ball-milled carbon nanotube dispersed aluminum mixed powders - Maleque, Md. Abdul; Abdullah, Umma; Yaacob, Iskandar Idris; Ali, Yousaf (IOP Publishing, 2016)
Currently, carbon nanotube (CNT) is attracting much interest as fibrous materials for reinforcing aluminum matrix composites due to unique properties, such as high strength, elastic modulus, flexibility and high aspect ratios. However, the quality of the dispersion is the major concerning factor which determines the homogeneity of the enhanced mechanical and tribological properties of the composite. This work study and characterized carbon nanotube dispersion in ballmilled CNT-aluminum mixed powders with four different formulations such as 1, 1.5, 2 and 2.5 wt% CNT under high energy planetary ball milling operations. The ball milling was performed for two hours at constant milling speed of 250 rpm under controlled atmosphere. The characterization is performed using FESEM and EDX analyzer for mapping, elemental and line analysis. The experimental results showed homogeneous dispersion of CNTs in aluminum matrix. The composite mixture showed similar pattern from mapping, elemental and line analysis. Identification of only two peaks proved that controlled atmosphere during milling prevented the formation of inter metallic compounds such as aluminum carbide in the composite mixture. Therefore, this CNT-Al composite powder mixture can be used for new nano-composite development without any agglomeration problem.